Study on the influence of fast moving ability and footwork on badminton - Zhong, H. (Frontiers in Sport Research, 2020)
As the basis of all the skills of badminton, footwork is particularly important, it is the soul of badminton. If you want to make flexible use of badminton techniques and tactics, you must have a solid footwork. The key of footwork lies in the athletes' ability to move quickly. The batting quality and initiative of athletes in the field are closely related to their own footwork and fast moving ability. The stronger the athletes' ability to move quickly, the more in place the hitting position on the field can be moved to avoid passive batting. It can make the batting movement of the player's hand more stable, let the ball fall on the opponent's court at the fastest speed, and put the opponent on the court. A more passive situation in the game. Good footwork can make athletes more coherent in the competition, reasonable use of footwork can also save physical strength and reduce energy consumption. Therefore, it is of great significance to improve the ability of fast movement and strengthen the practice of footwork for the improvement of sports technology.